2019
DOI: 10.1136/bmjopen-2019-031342
|View full text |Cite|
|
Sign up to set email alerts
|

Discontinuation of non-Vitamin K antagonist oral anticoagulants in patients with non-valvular atrial fibrillation: a population-based cohort study using primary care data from The Health Improvement Network in the UK

Abstract: ObjectiveTo determine discontinuation rates, patterns of use and predictors of discontinuation of non-vitamin K antagonist oral anticoagulants (NOACs) among patients with non-valvular atrial fibrillation (NVAF) in the first year of therapy.DesignPopulation-based cohort study.SettingUK primary care.Population11 481 patients with NVAF and a first prescription (index date) for apixaban, dabigatran or rivaroxaban (January 2012 to December 2016) with at least 1 year of follow-up and at least one further NOAC prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 36 publications
7
34
0
Order By: Relevance
“…Among RW DOAC initiators, the proportion of patients discontinuing treatment over a median follow-up of almost two years was 30% (versus 20% in RE-LY) for dabigatran, 20% (versus 24% in ROCKET AF) for rivaroxaban, and 16% (versus 25% in ARISTOTLE) for apixaban. Our results are in line with findings from recent observational studies [ 26 , 27 , 28 ]. In particular, a long-term study on the use of DOACs in clinical practice conducted by the Karolinska Institute showed that discontinuation rate was lower for apixaban (11.5, 7.5–16.8) users compared to rivaroxaban (23.9, 18.6–30.1, p -value = 0.001) and dabigatran (30, 23.4–37.9, p -value < 0.001 30%) users [ 26 ], in line with our results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among RW DOAC initiators, the proportion of patients discontinuing treatment over a median follow-up of almost two years was 30% (versus 20% in RE-LY) for dabigatran, 20% (versus 24% in ROCKET AF) for rivaroxaban, and 16% (versus 25% in ARISTOTLE) for apixaban. Our results are in line with findings from recent observational studies [ 26 , 27 , 28 ]. In particular, a long-term study on the use of DOACs in clinical practice conducted by the Karolinska Institute showed that discontinuation rate was lower for apixaban (11.5, 7.5–16.8) users compared to rivaroxaban (23.9, 18.6–30.1, p -value = 0.001) and dabigatran (30, 23.4–37.9, p -value < 0.001 30%) users [ 26 ], in line with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Other RW studies showed a higher rate of discontinuation than those seen in our study, but with the same trend among individual DOAC groups. A population-based cohort study using a UK primary care setting found that the discontinuation rates were respectively 40.0% for dabigatran, 29.6% for rivaroxaban, and 26.1% for apixaban during the first year of treatment [ 27 ]. A recent meta-analysis on RW data comparing persistence of DOAC users treated for NVAF showed that the pooled proportion of persistence for all follow-up durations (3–36 months) from 36 studies was 69% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in non-CHD patients, a significantly higher incidence of NOACs cessation has been described in both drug registration trials and real-life studies. For instance, 1-year discontinuation rate was 14% with apixaban [8] and 15% with dabigatran [6] during drug trials, while, in a recent real-life study in a large cohort in the UK, NOACs treatment cessation occurred in 26.1% of patients on apixaban, 40.0% on dabigatran and 29.6% on rivaroxaban at 1 year of follow-up [18]. One could speculate that ACHD patients are more likely to continue taking prescribed medication thanks to the health-related education they have received since childhood.…”
Section: Treatment Discontinuationmentioning
confidence: 98%
“…A UK population-based cohort study of 11,481 patients with AF who were treated with a DOAC between January 2012 and December 2016 found that almost a third of patients had discontinued DOAC treatment within 1 year. [ 16 ] The majority of these patients (60.4%) had a gap of at least 30 days without stroke protection before eventually reinitiating treatment with a vitamin K antagonist or DOAC. However, a significant percentage (n=813, 7.1%) still remained without anticoagulation following this period.…”
Section: Demand For Left Atrial Appendage Occlusion In the Ukmentioning
confidence: 99%